2006
DOI: 10.1136/gut.2005.080523
|View full text |Cite
|
Sign up to set email alerts
|

Wotherspoon criteria combined with B cell clonality analysis by advanced polymerase chain reaction technology discriminates covert gastric marginal zone lymphoma from chronic gastritis

Abstract: Background and aims: Gastric mucosa associated lymphoid tissue lymphoma is a well defined B cell lymphoma yet often impossible to distinguish from severe chronic gastritis on morphological grounds alone. Therefore, it was suggested to use the clonality of the immunoglobulin (Ig) heavy chain (H) genes, as detected by polymerase chain reaction (PCR), as a decisive criterion. However, there is controversy as to whether B cell clonality also exists in chronic gastritis, hence rendering this approach futile at pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…99 This recommendation was supported by another report 100 stating that a combination of the morphologic scoring system and B cell clonality analysis by an advanced PCR method accurately discriminated chronic gastritis from covert gastric marginal zone lymphoma. Polymerase chain reaction was particularly valuable in the interpretation of cases that exhibited an ambiguous score of grade 3 or 4.…”
Section: Gastric Lymphomas Especially Marginal Zone Lymphomas Of Malsupporting
confidence: 61%
“…99 This recommendation was supported by another report 100 stating that a combination of the morphologic scoring system and B cell clonality analysis by an advanced PCR method accurately discriminated chronic gastritis from covert gastric marginal zone lymphoma. Polymerase chain reaction was particularly valuable in the interpretation of cases that exhibited an ambiguous score of grade 3 or 4.…”
Section: Gastric Lymphomas Especially Marginal Zone Lymphomas Of Malsupporting
confidence: 61%
“…Others, including the original BIOMED-2 study, have shown that the use of a smaller amount of DNA (80 -300 ng per reaction) from cutaneous and gastric biopsies can be adequate to detect T-cell clonality. 8,28,29 Since the initial validation of BIOMED-2 primers was performed in both fresh/frozen and paraffinembedded tissue using 100 ng of DNA, 15 we used 184 Ϯ 146 ng of DNA (mean Ϯ SD; range: 10 -920 ng) per 25 l reaction based on the size of tissue compared with 500 to 2000 ng per 50 l reaction that is recommended by the manufacturer (InVivoScribe Technologies). It is possible that this lower amount of DNA is optimal for mono-V but not for multi-V PCR amplification of TCR-␥ V11.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal population have been found in cases of uncomplicated H. pylori-associated gastritis, 14 although the frequency of detection of such clonal populations increases with an increasing certainty for a diagnosis of lymphoma. 15 Immunophenotypically, the cells of MALT lymphoma show a rather non-descript B-cell phenotype. The cells express pan-B-cell markers (CD19, CD20, CD79a and PAX5) and BCL2.…”
Section: Extranodal Marginal Zone Lymphoma Of Mucosa-associated Lymphmentioning
confidence: 99%